Madagascaromyces cannae sp. nov. (Mycosphaerellaceae) on Canna indica (Cannaceae) from Guangdong, China - Chen, Jingwen; Manawasinghe, Ishara S.; Lin, Jieying; Lin, Yanhong; Wanasinghe, Dhanushka N.; Zhang, Yunxia (Phytotaxa, 2022)
Microfungi associated with Cannaceae are distributed in tropical and subtropical regions. Even though many fungal taxa have been reported from Cannaceae hosts, Mycospharellaceae on Canna indica are less studied. In this study, a saprobic Mycosphaerellaceae species was isolated on C. indica, from Guangzhou, Guangdong province, China. To identify the species, morphological characteristics and phylogenetic analysis of LSU, ITS and rpb2 were employed. Based on multi-gene phylogenetic analyses and morphological comparisons, we introduce our collection as a new species, Madagascaromyces cannae. The novel species is characterized by the septate, pale brown conidiophores, pale brown, terminal and lateral conidiogenous cells and pale brown, clavate, guttulate conidia with 0–6 septa. In addition, a detailed comparison of morphological characters of Madagascaromyces species is provided. To our knowledge, this is the first report of a Madagascaromyces species associated with C. indica in China. Our collection will be an addition to the knowledge of fungi associated with Cannaceae.